Developing a Digital Science E-magazine Based on Socioscientific Issues: Validity, Practicality, and Students’ Responses - Yokhebed; Harun Asyrofi; Anita Tri Andriani; Nova Siswanti adtya; Amelia Dwi Kartika; Li Yeqin (Universitas Syiah Kuala, 2026)
This research aims to develop a digital e-magazine based on socioscientific issues (SSI) in junior high schools. The research employed a Research and Development (R&D) approach using the 4D (define, design, develop, and disseminate) model. The product was designed using Heyzine as a platform, integrating text, images, videos, and interactive quizzes. The e-magazine content focused on the human organ systems aligned with the national curriculum and contextualized through relevant SSI topics such as smoking, drug abuse, junk food, and unhealthy lifestyles. The validation process involved seven science teachers as experts, and data were analyzed using Aiken’s validity index. The practicality and students’ perceptions were tested through small- and large-scale trials involving 9 and 106 students, respectively. The validation results obtained an average Aiken’s validity index of 0.88, indicating validity. The practicality test showed positive responses in terms of usability, clarity, and attractiveness. In the large-scale trial, students’ responses to the e-magazine reached an average of 93%, categorized as very good across cognitive, affective, and conative aspects. These findings suggest that the SSI-based e-magazine is a valid, practical, and well-received learning resource, effectively supporting students’ understanding, motivation, and engagement in science learning.